Positive intergroup contact, negative intergroup contact, and threat as predictors of cognitive and affective dimensions of prejudice. (November 2015) - Aberson, Christopher L.
Research on intergroup contact suggests that contact relates more strongly to affective than cognitive dimensions of prejudice. However, work on these forms of prejudice focuses primarily on positive contact experiences. One goal of this study is to examine whether positive and negative contact experiences differentially predict affective and cognitive dimensions of prejudice. The second goal is to examine intergroup threats as mediators of contact–prejudice relationships. Results demonstrated that negative contact more strongly predicted cognitive dimensions of prejudice such as stereotypes. Both types of contact were similarly predictive of affective dimensions of prejudice. The mediation of the negative contact–prejudice relationship was stronger across all dependent measures than mediation of the positive contact–prejudice relationship. Together these results suggest that either form of contact predicts affective prejudice but negative contact is particularly important in explaining cognitive dimensions of prejudice. Additionally, results suggest an important role for feelings of threat in explaining contact–prejudice relationships.